Selected ion monitoring/isotope dilution mass spectrometric determination of 1-aminocyclopropane-1-carboxylic acid levels in ripening tomato fruit - McGaw, Brian A.; Horgan, Roger; Heald, Jim K. (Analytical biochemistry, 1985)
A new method is described for the quantitation of 1-aminocyclopropane-1-carboxylic acid (ACC), the immediate precursor of ethylene in plants. [2,2,3,3,- 2H 4]ACC has been synthesized and used as an internal standard for selected ion monitoring/isotope dilution quantitation of this compound in ripening tomato fruit. These data are compared with those derived from the widely used indirect oxidative ACC assay (which underestimated the ACC levels by between two- and fourfold). The greater accuracy, sensitivity (100X), and specificity of the mass spectrometric method will be of considerable benefit to those interested in factors which control ACC and ultimately ethylene levels since it is believed that ACC synthesis and its oxidative metabolism to ethylene are the key points at which ethylene biosynthesis is regulated.